Analisis Struktur Modal, Likuiditas, dan Karakteristik Perusahaan terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Intervening serta Sustainability Disclosure sebagai Variabel Moderasi pada Perusahaan Sub Sektor Ritel yang Terdaftar di Bursa Efek Indonesia - Diva Damai Maharani; Hwihanus Hwihanus (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
This study aims to analyze the influence of capital structure, liquidity, and company characteristics on firm value, with profitability as an intervening variable and sustainability disclosure as a moderating variable, in retail sub-sector companies listed on the Indonesia Stock Exchange for the 2021-2025 period. This research is motivated by the decline in the average value of retail sub-sector companies, as reflected in Price to Book Value (PBV), necessitating an analysis of the factors influencing firm value. This study uses a quantitative approach with explanatory research methods. The data used are secondary data obtained from annual financial reports and company sustainability reports. The study population consisted of 32 retail sub-sector companies selected using purposive sampling during the 2021-2025 period, resulting in 40 observations. Data analysis was performed using the Principal Least Squares (PLS) method with the assistance of SmartPLS software. The result show that capital structure has a negative but insignificant effect on firm value and a positive but insignificant effect on profitability. Liquidity has a positive and significant effect n profitability, but a negative and significant effect on firm value. Company characteristics have a positive and significant effect on both profitability and firm value. Profitability does not significantly influence firm value. Furthermore, sustainability disclosure is unable to moderate the effect of profitability on firm value. The findings of this study indicate that company characteristics and liquidity are important factors in increasing profitability and firm value.